Thailand - Towards a Competitive Higher Education System in a Global Economy - World Bank (World Bank, 2012)
The global economy has become increasingly complex and competitive. Many countries have turned to knowledge-based growth to transition from labor-intensive sectors to new and emerging economic activities that require higher skills and intellectual capital. In Thailand, higher education increasingly plays an essential role in enabling greater opportunities for economic growth and attractiveness to foreign investment. This social monitor provides a snapshot of the current state of the higher education sector in Thailand by examining its key characteristics, latest developments, strengths, and weaknesses. It also focuses on the extremely important relationships between higher education, research and development, innovation policies, and the private sector. In short, Thailand can rightfully point to major achievements in the development of its higher education system, including the establishment of autonomous universities and increasing access through innovative open universities such as Rajabhat and Rajamangala. However, the higher education system faces many challenges in the areas of governance, financing, quality, access, and its relationship to the private sector. Without significant changes in both policies and attitudes in these areas, Thailand's future vision as a knowledge-based economy relying on highly skilled labor and technological advances to drive growth and productivity will be extremely difficult to achieve.